Pembinaan Kesehatan Ibu Dan Anak Melalui Deteksi Dini Tumbuh Kembang Anak (SDIDTK) - AGUNG SUHARTO; Sulikah Sulikah; Tinuk Esti H; Suparji; Budi Joko S (Poltekkes Kemenkes Surabaya, 2022)
Implementation of SDIDTK, from information obtained that only around 30% of toddlers have implemented SDIDTK. There are 10 high-risk pregnant women. Exclusive breastfeeding data in Milangasri Village is quite low. The purpose of this community service is to help Milangasri Village in solving maternal and child health problems as a form of social care in the form of Community Development in Milangasri Village. This community service method is a survey and health education. From the data analysis, the formulation of the problem can be formulated as follows: Implementation of SDIDTK, from information obtained that only about 30% of children under five who have implemented SDIDTK therefore want to implement SDIDTK for toddlers who have not. There are 39 pregnant women, so they want to carry out continuity care for pregnant women, starting from the first trimester, during childbirth, after childbirth, until they decide to use family planning in the form of mentoring by students, under the guidance of lecturers and local village midwives. In conclusion, this community service is very much needed to improve the fulfillment of MCH/KB as well as the growth and development of children